Measuring Walkability – Analysis of Institutional Campuses: Examining the Relationship Between Spatial Configuration and Walkability on Institutional Campuses (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Walking is a significant mode of commuting on institutional campuses. The designed network ofroads, footpaths, and open spaces promotes a walkable environment. This research analyzes aninstitutional campus layout in multiple ways – 1) Studying the plan and predicting the pedestrian andvehicular circulation pattern. 2) Observing and recording current pedestrian and vehicular circulationpatterns 3) Conducting surveys and interviews of the users to understand the issues and designconsiderations of the campus walkability.The research highlights the relationship between spatial configuration and walkability and how thespatial configuration can be modified to achieve a better walkable environment for the user. The studyattempts to understand the characteristics of the built environment that encourage a walkable climate byanalyzing users' perceptions.The research adopts qualitative and quantitative methods to analyze walkable environments oneducational campuses. Parameters for measuring walkability were listed, and a questionnaire surveywas prepared to measure user perception. The research attempts to understand the walkabilitymeasures and the effect of spatial configuration on human behavior.